1981
DOI: 10.1093/jn/111.6.1067
|View full text |Cite
|
Sign up to set email alerts
|

Species Specificity of Arginine Deficiency-Induced Hepatic Steatosis

Abstract: Hepatic steatosis resulting from the consumption of an arginine-deficient diet in the rat was found to occur independent of age or size. The rate of lipid biosynthesis as indicated by in vitro incorporation of 14C-acetate was significantly increased in rats fed an arginine-deficient diet when expressed per milligram liver. Supplementation of the arginine-deficient diet with 1% ribose, 1% hypoxanthine or 0.2% adenine depressed the fatty infiltration caused by arginine deficiency. Inosine, xanthine or uracil sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The inverse relationship between arginine levels and hepatic TG content may be due to increased arginine degradation in steatotic mice. Previous studies have shown that an arginine-deficient diet-induced hepatic steatosis in rats ( Milner and& Hassan, 1981 ). The levels of arginase 1, which catabolizes L-arginine to urea and L-ornithine, were increased in steatotic livers from mice fed a high-fat diet ( Eccleston et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inverse relationship between arginine levels and hepatic TG content may be due to increased arginine degradation in steatotic mice. Previous studies have shown that an arginine-deficient diet-induced hepatic steatosis in rats ( Milner and& Hassan, 1981 ). The levels of arginase 1, which catabolizes L-arginine to urea and L-ornithine, were increased in steatotic livers from mice fed a high-fat diet ( Eccleston et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding an arginine-defi cient diet to rats leads to a marked fatty liver by an elevated plasma concentration of OA. Additionally, mice, hamsters, and rabbits were resistant to fatty liver largely because of their high urinary excretion rate of OA ( 45 ). Apart from this pharmacokinetic issue, no other information has been available concerning species-specifi c mechanisms of OA hepatotoxicity.…”
Section: Rapamycin Inhibits Oa-induced Fatty Livermentioning
confidence: 99%
“…Male Sprague-Dawley rats that are fed an argininedeficient diet for 21 days have significantly decreased rates of body weight gain but increased rates of hepatic lipid biosynthesis and urinary excretion of orotic acid and develop markedly fatty livers regardless of their age. 69 Supplementation of the arginine-deficient diet with 1% ribose, 1% hypoxanthine, or 0.2% adenine suppresses urinary orotic acid excretion and decreases the fatty infiltration, whereas supplementation with inosine, xanthine, or uracil does not. Although argininedeficient diets increase urinary orotic acid excretion in mice, hamsters, and rabbits, these species do not develop overtly fatty livers.…”
Section: Arginine-deficient Dietsmentioning
confidence: 99%